PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PENANGANAN PRASARANA DAN SARANA UMUM (PPSU) PADA KANTOR KELURAHAN PONDOK LABU JAKARTA SELATAN - Harun Al Rasyid; Syarifah Ida Farida (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The purpose of this study was to determine the effect of the Work Environment and Work Discipline on the Performance of Public Infrastructure and Facilities Handling (PPSU) employees at the Pondok Labu Urban Village Office, South Jakarta. This study employed a quantitative approach. The sampling technique used was saturated sampling, with a total of 67 respondents. The data analysis methods included validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results showed that the Work Environment had a positive and significant effect on Employee Performance, as indicated by a t-value of 14.403, which was greater than the t-table value of 1.997. Work Discipline also had a positive and significant effect on Employee Performance, as indicated by a t-value of 19.753, which was greater than the t-table value of 1.997. Furthermore, the Work Environment and Work Discipline simultaneously had a positive and significant effect on Employee Performance, as indicated by an F-value of 197.815, which was greater than the F-table value of 2.74. These findings indicate that the Work Environment and Work Discipline are important factors in improving the performance of PPSU employees at the Pondok Labu Urban Village Office, South Jakarta.